Home bound : Filipino American lives across cultures, communities, and countries - Espiritu, Yen Le, 1963- (University of California Press, 2003)
Filipino Americans, who experience life in the United States as immigrants, colonized nationals, and racial minorities, have been little studied, though they are one of our largest immigrant groups. Based on her in-depth interviews with more than one hundred Filipinos in San Diego, California, Yen Le Espiritu investigates how Filipino women and men are transformed through the experience of migration, and how they in turn remake the social world around them.